Myocardial work brings a new insight into left ventricule remodelling in cardiooncology patients. (8th February 2021) - Ferreira, V; Cruz Coutinho, M; Moura Branco, L; Galrinho, A; Timoteo, AT; Rio, P; Almeida Morais, L; Aguiar Rosa, S; Duarte Oliveira, S; Leal, A; Castelo, A; Garcia Bras, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Serial echocardiographic assessment of 2D left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) is the gold standard screening method for cancer therapeutics-related cardiac dysfunction (CTRCD). Non-invasive left ventricular (LV) pressure-strain loop (PSL) provides a novel method of quantifying myocardial work (MW) with potential advantages, as it incorporates measurements of myocardial deformation and LV pressure. Purpose: To evaluate the impact of cardiotoxic treatments in MW indices. Methods: Prospective study of female breast cancer patients (P) submitted to therapy (TH) who underwent serial monitoring by 2D, 3D transthoracic echocardiography (TTE) and concomitant blood pressure assessment. P were evaluated at T0, T1 and T2 (before, ≥6 and ≥12 months after starting TH). PSL analysis allowed the calculation of the following indices: Global Work Index (GWI), Global Constructive Work (GCW), Global Work Waste (GWW) and Global Work Efficiency (GWE). CTRCD was defined as an absolute decrease in 2D LVEF > 10% to a value < 54% or a relative decrease in 2D GLS > 15%, according to literature.  Results: 122 patients (mean age 54.7 ± 12.0 years), mostly treated with anthracyclines (77.0%, cumulative dose 268.6 ± 71.8mg/m2), anti-HER (75.4%) and radiotherapy (77.0%) were included. 2D and 3D LVEF were significantly reduced during TH, however remaining within the limits of normality (2D LVEF T0-T1 64.2 ±7.6 vs 61.1 ± 8.2%, p = 0.006 and 3D LVEF T0-T1 60.2 ± 6.7 vs 56.9 ±6.3%, p = 0.022). 2D GLS was also more impaired at T1 (-19.8 ± 2.7% vs -18.5 ± 3.0%, p = 0.003). All MW indices were significantly reduced at T1 compared to baseline (GWI 1756.9 ± 319.2 vs 1614.3 ± 338.5mmHg%, p = 0.005; GCW 2105.6 ± 352.0 vs 1970.5 ± 376.2 mmHg%, p = 0.015; GWW 121.1 ± 66.6 vs 161.1 ± 84.1 mmHg%, p = 0.001; GWE 93.5 ± 3.1 vs 91.1 ± 4.5%, p = 0.001). Between T1 and T2 no statistical difference was found but a partial recovery of parameters was observed when comparing T2 to T0 (GWI (T2) 1650.6 ± 357.5 mmHg%, p = 0.035; GCW (T2) 2013.3 ± 379.3 mmHg%, p = 0.086; GWW (T2) 148.0 ± 85.0 mmHg%, p = 0.02 and GWE (T2) 92.0 ± 4.7%, p = 0.012).  During a mean follow-up of 14.9 ± 9.3 months, 36 patients (29.5%) developed CTRCD.  P presenting CTRCD revealed a significant decrease in GWI and GWE at T1 comparing with women without CTRCD (GWI 1.8 ± 21.6 vs -14.2 ± 18.5%, p = 0.004 and GWE -1.0 ±3.0 vs -3.6 ±3.9%, p = 0.005). GWW had a substantially increase at T1 in P with cardiotoxicity (27.6 ± 76.3% vs 64.1 ± 68.0%, p = 0.051). Conclusion: Left ventricular systolic function study with MW showed a reduction in cardiac performance with a peak at 6 months from the start of chemotherapy and partial recovery after term. Assessment of myocardial deformation parameters, namely MW, proved to be a useful tool for a better characterisation of cardiac remodelling, and could enhance patient selection for cardioprotective therapeutics.